2018
DOI: 10.1186/s12889-018-5770-5
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of Family Group Conferencing in child welfare: a controlled study

Abstract: BackgroundThis study aimed to examine the short- and long term (cost-) effectiveness of Family Group Conferencing (FGC) compared to care as usual (CAU) in terms of improved child safety, empowerment and social support.MethodsA subgroup of a larger randomized controlled trial, comprising 69 families in child welfare (experimental group: n = 46; control group: n = 23), was included.ResultsNo additional effects of FGC on child safety, social support and only short-term positive effects on empowerment were found. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 20 publications
0
25
0
1
Order By: Relevance
“…Our second aim was to investigate study designs used where randomisation was not appropriate. Fifteen of the 21 studies used data from RCTs where participants were randomised into intervention or control groups at recruitment (Ammerman et al, 2017;Aracena et al, 2009;Au et al, 2006;Barlow et al, 2007Barlow et al, , 2019Bell et al, 2019;Browne et al, 2001;Dalziel et al, 2015;Deidda et al, 2018;Dijkstra et al, 2018;Kuklinski, Oxford, et al, 2020;McIntosh et al, 2009;Sharac et al, 2011;Sonuga-Barke et al, 2018). In Kuklinski, Crowley, et al (2020) the study was based on an RCT; however only the intervention group was investigated.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Our second aim was to investigate study designs used where randomisation was not appropriate. Fifteen of the 21 studies used data from RCTs where participants were randomised into intervention or control groups at recruitment (Ammerman et al, 2017;Aracena et al, 2009;Au et al, 2006;Barlow et al, 2007Barlow et al, , 2019Bell et al, 2019;Browne et al, 2001;Dalziel et al, 2015;Deidda et al, 2018;Dijkstra et al, 2018;Kuklinski, Oxford, et al, 2020;McIntosh et al, 2009;Sharac et al, 2011;Sonuga-Barke et al, 2018). In Kuklinski, Crowley, et al (2020) the study was based on an RCT; however only the intervention group was investigated.…”
Section: Methodsmentioning
confidence: 99%
“…We found that more than half the included papers were withintrial cost-effectiveness analyses (Aracena et al, 2009;Barlow et al, 2007Barlow et al, , 2019Dalziel et al, 2015;Dijkstra et al, 2018;Mathewos et al, 2017;McIntosh et al, 2009;Sharac et al, 2011;Sonuga-Barke et al, 2018;Thanh et al, 2015). Cost effectiveness analysis is one of the most commonly used economic analysis methodologies in healthcare, and is concerned with the differential comparison of costs and effects by calculating an incremental cost-effectiveness ratio (ICER) (Elliot & Payne, 2005).…”
Section: Within-trial Cost-effectivenessmentioning
confidence: 99%
See 3 more Smart Citations